2021
DOI: 10.1111/jonm.13309
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to participate in front‐line work during the COVID‐19 pandemic: A cross‐sectional study of nurses from a province in South‐West China

Abstract: Aim To explore the current status of Chinese nurses’ willingness to work during the COVID‐19 pandemic and the factors that influence them. Background The demand for front‐line nurses continues to grow during the COVID‐19 pandemic, but their willingness varies significantly. Therefore, it is crucial to explore nurses’ willingness to report for front‐line work. Methods A cross‐sectional study of 1,310 nurses from six tertiary hospitals was conducted. The participants completed self‐administered online questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…The included manuscripts were published between 2003 and 2021. As shown in Table 1 , studies were conducted in various countries, including Australia ( n = 4) [ 8 , 22 , 23 , 24 ], Bangladesh ( n = 1) [ 25 ], Canada ( n = 1) [ 26 ], China ( n = 7) [ 2 , 7 , 27 , 28 , 29 , 30 , 31 ], Georgia ( n = 1) [ 32 ], Hong Kong ( n = 1) [ 33 ], Nigeria ( n = 1) [ 34 ], Pakistan ( n = 1) [ 35 ], Philippines ( n = 1) [ 36 ], Qatar ( n = 1) [ 37 ], South Korea ( n = 2) [ 38 , 39 ], Taiwan ( n = 3) [ 4 , 40 , 41 ], Turkey ( n = 1) [ 42 ], USA ( n = 3) [ 5 , 43 , 44 ], and Yemen ( n = 1) [ 15 ]. Among the 29 studies reviewed, 19 studies included nurses only [ 4 , 5 , 8 , 22 , 27 , 28 , 29 , 30 , 31 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included manuscripts were published between 2003 and 2021. As shown in Table 1 , studies were conducted in various countries, including Australia ( n = 4) [ 8 , 22 , 23 , 24 ], Bangladesh ( n = 1) [ 25 ], Canada ( n = 1) [ 26 ], China ( n = 7) [ 2 , 7 , 27 , 28 , 29 , 30 , 31 ], Georgia ( n = 1) [ 32 ], Hong Kong ( n = 1) [ 33 ], Nigeria ( n = 1) [ 34 ], Pakistan ( n = 1) [ 35 ], Philippines ( n = 1) [ 36 ], Qatar ( n = 1) [ 37 ], South Korea ( n = 2) [ 38 , 39 ], Taiwan ( n = 3) [ 4 , 40 , 41 ], Turkey ( n = 1) [ 42 ], USA ( n = 3) [ 5 , 43 , 44 ], and Yemen ( n = 1) [ 15 ]. Among the 29 studies reviewed, 19 studies included nurses only [ 4 , 5 , 8 , 22 , 27 , 28 , 29 , 30 , 31 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , …”
Section: Resultsmentioning
confidence: 99%
“…Among the 29 studies reviewed, 19 studies included nurses only [ 4 , 5 , 8 , 22 , 27 , 28 , 29 , 30 , 31 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], 6 included physicians only [ 23 , 24 , 25 , 26 , 34 , 35 ], and 4 included both nurses and physicians [ 2 , 7 , 15 , 32 ]. A total of 19 studies were conducted during an outbreak or pandemic, such as the SARS outbreak ( n = 2) [ 4 , 41 ], the H1N1 influenza pandemic ( n = 3) [ 5 , 33 , 43 ], the Middle East respiratory syndrome (MERS) outbreak ( n = 1) [ 39 ], and the COVID-19 pandemic ( n = 13) [ 2 , 7 , 8 , 25 , 27 , 28 , 29 , 30 , 31 , 35 , 36 , 37 , 42 ]. One study was conducted to evaluate the high possibility of an avian influenza (AI) outbreak [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have been inconsistent regarding the association of professional experience with nurses’ willingness to participate in fighting the epidemic [ 12 , 32 ]. The results of multiple logistic regression analysis showed that a predictor was not professional experience, but rather professional title.…”
Section: Discussionmentioning
confidence: 99%